2023
DOI: 10.1111/cobi.14066
|View full text |Cite
|
Sign up to set email alerts
|

Importance of conserving large and old trees to continuity of tree‐related microhabitats

Abstract: Protecting structural features, such as tree-related microhabitats (TreMs), is a cost-effective tool crucial for biodiversity conservation applicable to large forested landscapes. Although the development of TreMs is influenced by tree diameter, species, and vitality, the relationships between tree age and TreM profile remain poorly understood. Using a tree-ring-based approach and a large data set of 8038 trees, we modeled the effects of tree age, diameter, and site characteristics on TreM richness and occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…We found no relationships between TreM numbers and slope inclination or elevation. A higher elevation may alter local rainfall and humidity, promoting tree cavity and epiphyte formation (Remm and Lõhmus, 2011; Kozák et al, 2023). Steep mountain slopes can be the cause of tree trunk damage due to rockfall (Šilhán, 2010), which leads to the development of reactive wood and asymmetrical root systems, and also the formation of root buttress cavities (Young and Perkocha, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…We found no relationships between TreM numbers and slope inclination or elevation. A higher elevation may alter local rainfall and humidity, promoting tree cavity and epiphyte formation (Remm and Lõhmus, 2011; Kozák et al, 2023). Steep mountain slopes can be the cause of tree trunk damage due to rockfall (Šilhán, 2010), which leads to the development of reactive wood and asymmetrical root systems, and also the formation of root buttress cavities (Young and Perkocha, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These were the only two structures for which the effect of management was positive, which was expected as pine and spruce are the most important commercial tree species in Sweden, and management specifically aims to promote their growth. However, the increased amount of large conifers in managed forests is likely of limited importance for biodiversity, since the trees are typically harvested before they reach a sufficiently old age to develop specific microhabitats that host specialized species (Paillet et al 2017 ; Kozák et al 2023 ), and since many species that inhabit living trees require longer time for colonization than the current rotation periods allow (Kuusinen and Siitonen 1998 ; Marmor et al 2011 ). The positive effect of management also decreased with productivity, thus changing the relationship between productivity and the amount of large conifers.…”
Section: Discussionmentioning
confidence: 99%
“…epiphytic lichens and bryophytes, insects, and cavity-dwelling birds (e.g. Paillet et al 2017 ; Kozák et al 2023 ). Thus, the amount and diversity of such structures can function as a proxy for forest biodiversity (Larrieu et al 2018 ; Hekkala et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated LOT's critical role in maintaining biodiversity, ecological balance, cultural heritage, and scientific research (Jim, 2017 ; Lindenmayer, 2017 ). They support a wide array of companion life forms such as lichen, moss, and fungus due to their structural complexity and sheer size, providing a diverse assortment of microhabitats to support many species, including rare and endangered ones (Kozák et al., 2023 ; Le Roux et al., 2014 ; Lindenmayer, 2017 ). In urban areas, preserving large trees can effectively conserve local biodiversity (Stagoll et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%